The history of the study of landforms, or, The development of geomorphology. Vol 1: Geomorphology before Davis [electronic resource] - Chorley, Richard J.; Beckinsale, R. P. [ (Robert Percy)]; Dunn, Antony J. (Routledge revivals, 2009)
This re-issue, first published in 1964, is the first of a seminal series analysing the development of the study of landforms, from both the geographical and geological point of view, with especial emphasis upon fluvial geomorphology. Volume 1 treats the subject up to the first important statement of the cycle of erosion by W. M. Davis in 1889, and attempts to identify the most significant currents of geomorphic